2014
DOI: 10.2105/ajph.2013.301361
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Randomized Controlled Trial Evaluation of Universal Postnatal Nurse Home Visiting

Abstract: Objectives We evaluated whether a brief, universal, postnatal nurse home-visiting intervention can be implemented with high penetration and fidelity, prevent emergency health care services, and promote positive parenting by infant age 6 months. Methods Durham Connects is a manualized 4- to 7-session program to assess family needs and connect parents with community resources to improve infant health and well-being. All 4777 resident births in Durham, North Carolina, between July 1, 2009, and December 31, 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
141
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 20 publications
4
141
1
7
Order By: Relevance
“…A study of Durham Connects (also known as Family Connects) showed more than 80% participation and 84% adherence among all mothers delivering in Durham, North Carolina, during an 18-month period. 51 Researchers in this study, using rigorous methodology, documented important and beneficial effects on child health, including a 59% reduction in emergency medical care, an increase in positive parenting, successful linkages to community services, and by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from improved maternal mental health. In addition, a large-scale study of SafeCare home-based services showed reductions in reports to child protective services after a scale-up of the program in Oklahoma.…”
Section: National Evaluation and Evidence Of Effectivenessmentioning
confidence: 95%
“…A study of Durham Connects (also known as Family Connects) showed more than 80% participation and 84% adherence among all mothers delivering in Durham, North Carolina, during an 18-month period. 51 Researchers in this study, using rigorous methodology, documented important and beneficial effects on child health, including a 59% reduction in emergency medical care, an increase in positive parenting, successful linkages to community services, and by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from improved maternal mental health. In addition, a large-scale study of SafeCare home-based services showed reductions in reports to child protective services after a scale-up of the program in Oklahoma.…”
Section: National Evaluation and Evidence Of Effectivenessmentioning
confidence: 95%
“…A final session 4 weeks after the nurse completes the case reinforces community connections. Dodge et al 8 reported that 80% of all families assigned to DC consented and began participation, with 86% of the consenting group completing the entire program (net completion = 69%). Of these families, 40% were European American, 37% were African American, and 23% were other or multiracial, with 26% reporting Hispanic ethnicity; 62% received Medicaid or had no health insurance, and 49% were married.…”
Section: The Durham Connects Programmentioning
confidence: 99%
“…Problems in community-wide implementation have been overcome by the Durham Connects (DC) program, 8 which was designed in collaboration with community leaders and piloted at the population level before evaluation by a randomized controlled trial (RCT). DC is a short-term, universal, inexpensive ($700 per family) postnatal nurse home visiting program designed to provide brief parenting intervention and to connect families with community resources based on individualized assessments of family needs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Durham Connects program is a 4-7 session manualized program that addresses family needs in home and connects high-risk parents with community resources to improve infant health and well being. Several randomized controlled trials have found that program participants report fewer infant emergency care visits, more community connections, more positive parenting behaviors, and lower rates of mental health problems such as anxiety than the control group (Dodge et al, 2014). (See Table 3.…”
Section: The Early Years (Ages 0-5): Parenting and Child-centered Daymentioning
confidence: 99%